The governess in nineteenth-century Ulster middle-class households. Issue 5 (29th July 2022) - Devlin, Shannon
ABSTRACT: With its focus on Ulster middle-class households, this article traces the experience of Irish, English, and European governesses in nineteenth-century Ulster society. Using correspondence between governesses and their employers found in family papers, this article gives voice to the governess and uncovers her multifaceted roles within the household. As the century progressed, shifting expectations put pressure on governesses to provide a more academic education to their charges whilst also retaining the sophistication of elite middle-class gentility. Most governesses undertook duties beyond the role of educator and integrated themselves into the lives of both their employer and the children they were teaching. These close, long-standing relationships could be utilised for further employment, social networking, and be depended upon after employment. Often seen as positioned on the periphery of the family, this article argues that governesses had an important role in shaping family relationships and the household.